2009
DOI: 10.1063/1.3043818
|View full text |Cite
|
Sign up to set email alerts
|

Franck–Condon analysis of laser-induced fluorescence excitation spectrum of anthranilic acid: Evaluation of geometry change upon S→S1 excitation

Abstract: Geometry and vibrational modes of the anthranilic acid molecule in the S(0) and S(1) states were computed using ab initio methods: Hartree-Fock (HF) and configuration interaction of singly excited configurations (CIS) as well as the density functional theory with time-dependent perturbation (TD-DFT). The intensity distribution in the laser-induced fluorescence excitation spectra was modeled in two ways: using displacement parameters for independent modes and using multidimensional Franck-Condon integrals. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 54 publications
5
29
0
Order By: Relevance
“…In spite of the uncertainty caused by the presence of two closely lying bands and significant anharmonicity, it can be concluded that the 6S mode possesses a relatively large isotopic shift, consistent with the shift of the computed vibrational frequency. This supports the assignment of the band at 594:6 cm À1 (AA) to the 6S mode [13,14]. Moreover, the assignment of this band to the combination of overtones of out-of-plane modes 2 Â 2A + 2 Â 3A [4] is not supported by relative band intensities.…”
Section: Deuteration Shifts Of Fundamental Bandssupporting
confidence: 63%
See 4 more Smart Citations
“…In spite of the uncertainty caused by the presence of two closely lying bands and significant anharmonicity, it can be concluded that the 6S mode possesses a relatively large isotopic shift, consistent with the shift of the computed vibrational frequency. This supports the assignment of the band at 594:6 cm À1 (AA) to the 6S mode [13,14]. Moreover, the assignment of this band to the combination of overtones of out-of-plane modes 2 Â 2A + 2 Â 3A [4] is not supported by relative band intensities.…”
Section: Deuteration Shifts Of Fundamental Bandssupporting
confidence: 63%
“…The spectrum of the deuterated anthranilic acid is shown on The modes are ordered according to increasing frequencies, so that consistency with the previously used notation [13,14] is maintained.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations